A volatile spray zone model and experimentation in a gas-solid fluidized bed with liquid injection. (15th February 2021) - Tian, Sihang; Sun, Jingyuan; Fan, Xiaoqiang; Yang, Yao; Huang, Zhengliang; Wang, Jingdai; Yang, Yongrong
Graphical abstract: Highlights: The liquid existence forms and fluidization properties in the volatile spray zone. A mesoscale-theory based volatile spray zone model is proposed. Experiments on temperature and void fraction in the volatile spray zone are set up. The gas-solid drag coefficient is modified in the volatile spray zone. The mathematical and CFD models are validated through experimental results. Abstract: In a gas-solid fluidized bed, volatile liquid injection results in complex flow behaviors in the spray zone. To characterize the liquid existence forms (droplets and liquid films) and fluidization properties in the volatile spray zone, a mesoscale-theory based volatile spray zone model is developed with the consideration of hydrodynamics, heat transfer, and mass transfer. A new energy-based stability condition is established according to two competition and coordination relationships, consisting of the energy dissipation based on the liquid-solid interface change and suspension and transporting of particles. The modeling results agree well with the experimental bed temperature as well as void fraction data, and show that the variation of liquid existence forms is dependent on the ratio of different energy consumption rates under the stability condition. Moreover, the gas-solid drag coefficient in the volatile spray zone is modified. Simulation results also reasonably describe the bed pressure drop fluctuation and particle velocity distribution.